The Concept of Literacy in Lithuanian Language Textbooks for Native Speakers of Forms 1 to 4 Published in the Last Decades of the Soviet Era - Čičirkaitė, Ramune (Taikomoji kalbotyra, 2025)
This article describes a study that aims to clarify the features of the concept of literacy that has been influenced by the ideology of a standard language, as presented in Lithuanian language textbooks for native speakers of forms 1 to 4 that were published in the last decades of the Soviet Era. The textbooks from the last decades of the Soviet era were chosen as the study material after noticing that during this period the pedagogies in other countries began to critically reflect on the role of the ideology of a standard language when teaching native languages, as well as to rather rely on the insights of modern linguistics and to foster linguistic awareness based on a scientific approach to language. The study found that textbooks for forms 1 to 4 published during the last decades of the Soviet era display a normative approach to language and literacy that stems from and supports the ideology of a standard language: pupils are encouraged to reproduce only the standard language forms and not deviate from the standard, while linguistic diversity is ignored, not scientifically interpreted, and treated as an error. The ideology of a standard language has also influenced the concept of literacy presented in these textbooks, which is narrow and normative. Literacy was then understood as a mechanically acquired technical skill, developed through repeated practice of language forms, while being literate meant being able to write down standard language forms. The teaching of orthography, which was based on such assignments as addition of missing letters, rewriting and mechanical application of rules, was in line with the ideology of a standard language, whose aim was to unify and maintain a standardised language, in this case – written language. This aim also coincided with the Soviet regime’s goal of creating a controlled (linguistic) space and society. The narrow and normative notion of literacy has led to a reproductive type of language teaching and learning in forms 1 to 4, where the focus was rather on the form of written language rather than its content, relatively few assignments were devoted to the development of better skills of text production and editing, and there were no assignments that would encourage pupils to independently recognise, analyse, interpret and scientifically evaluate linguistic phenomena in real life. Thus, the textbooks analysed did not critically reflect on the role of the ideology of a standard language and did not develop children’s linguistic awareness based on a scientific approach to language.